2021
DOI: 10.1002/jgh3.12628
|View full text |Cite
|
Sign up to set email alerts
|

Safety, feasibility, and comfort of hepatic angiography and transarterial intervention with radial access for hepatocellular carcinoma

Abstract: Background and Aim Hepatic angiography procedures such as transarterial chemoembolization (TACE) are essential procedures for managing patients with hepatocellular carcinoma (HCC), and are usually performed with femoral access. However, femoral access causes patient discomfort and may be associated with the risk of hematoma or pseudoaneurysm at puncture site. We evaluated the safety, feasibility, and patient comfort of hepatic angiography procedures performed with radial access. Methods In this single‐institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…However, no difference was observed in the procedural success rate or complication rate. Toyoda et al reported that this technique can be learned in a year [ 6 ]. Patients aged 80 years had a history of and a higher risk for cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no difference was observed in the procedural success rate or complication rate. Toyoda et al reported that this technique can be learned in a year [ 6 ]. Patients aged 80 years had a history of and a higher risk for cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, compared with TFA, TRA has better outcomes in liver cancer treatment, is associated with a lower incidence of complications and a shorter hospital stay, and has medical economic advantages [4,5]. Recently, in Japan, TRA has been found to be safe and useful [6][7][8]. In addition to improving treatment efficacy, minimally invasive treatment is an important element in light of a recent medical trend.…”
Section: Introductionmentioning
confidence: 99%